1991
DOI: 10.1111/j.1439-0434.1991.tb01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascochitine Production by Fungi Responsible for Ascochyta Diseases of Pea

Abstract: Ascochitine production by 24 isolates of three fungal species causing the Ascochyta disease complex in pea plants, was examined. All eight isolates of Ascochyta pisi Lib. secreted ascochitine to liquid nutrient medium in amounts of 0.1 to 1.2 mg/l. However, no ascochitine was found in culture filtrates of Mycosphaerella pinodes (Berk. and Blox.) Vestergr. or of Phoma medicaginis var. pinodella (Jon.) Boerema although the aggressiveness of these two species as pathogens was shown to be higher than that of A. pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…All three types of compounds are produced by A. rabiei which has been studied most extensively (reviewed by Welle 1992 andJayakakumar et al 2005), and the toxins solanopyrones A, B and C have been isolated from culture filtrates and spore germination fluids (Hö hl et al 1991;Kaur 1995). The role of the phytotoxin ascochitine has been comprehensively studied on faba bean infected with A. fabae (Beed et al 1994), and on pea infected with A. pisi (Marcinkowska et al 1991). Suppressors (reviewed by Shiraishi et al 1994) and cell wall-degrading enzymes (Heath and Wood 1971a) were isolated and characterised from M. pinodes on pea leaves.…”
Section: Infection Processmentioning
confidence: 99%
“…All three types of compounds are produced by A. rabiei which has been studied most extensively (reviewed by Welle 1992 andJayakakumar et al 2005), and the toxins solanopyrones A, B and C have been isolated from culture filtrates and spore germination fluids (Hö hl et al 1991;Kaur 1995). The role of the phytotoxin ascochitine has been comprehensively studied on faba bean infected with A. fabae (Beed et al 1994), and on pea infected with A. pisi (Marcinkowska et al 1991). Suppressors (reviewed by Shiraishi et al 1994) and cell wall-degrading enzymes (Heath and Wood 1971a) were isolated and characterised from M. pinodes on pea leaves.…”
Section: Infection Processmentioning
confidence: 99%
“…Ascochitine ( 176 ; Figure ), a phytotoxic fungal metabolite, first isolated from cultures of Ascochyta pisi Lib. by Bertini, was later obtained from Ascochyta fabae Speg. by Oku and Nakanishi .…”
Section: Azaphilonesmentioning
confidence: 99%
“…A correlation was shown between the pathogenicity of A. pisi and the in vitro production of ascochitine (Lepoivre 1982). Marcinkowska et al (1991) also reported ascochitine production by A. pisi , but not by A. pinodes or Ascochyta pinodella . Fungi responsible for Ascochyta blight may be considered as hemibiotrophs, characterized by an initial biotrophic phase that is followed by a necrotrophic phase (Spoel et al 2007).…”
Section: Introductionmentioning
confidence: 96%